2012
DOI: 10.1074/jbc.m111.337931
|View full text |Cite
|
Sign up to set email alerts
|

Sorting Nexin 27 Interacts with Multidrug Resistance-associated Protein 4 (MRP4) and Mediates Internalization of MRP4

Abstract: Background:Little is known about the molecular mechanism regulating MRP4 expression on the cell surface. Results: SNX27 physically associates with MRP4 through PDZ-PDZ interaction and accelerates MRP4 internalization. Conclusion: SNX27 mediates MRP4 internalization and thereby negatively modulates the cell surface expression and transport function of MRP4. Significance: This study provides insights into the mechanisms responsible for MRP4 internalization and SNX27 function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…Modulation of endosomal retrieval or ubiquitination can regulate the change in the degradation rate of apical-surface-resident ABC transporters, thereby inducing their cell-surface expression and increasing their activity (89)(90)(91)(92).…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of endosomal retrieval or ubiquitination can regulate the change in the degradation rate of apical-surface-resident ABC transporters, thereby inducing their cell-surface expression and increasing their activity (89)(90)(91)(92).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the PX domain of these proteins binds with high specificity to PtdIns3P, driving their localization to PtdIns3P-enriched early endosomes Stockinger et al, 2002). PX-FERM proteins can then interact with cargo containing NPxY or NxxY motifs, and also PDZ-binding motif (PDZbm) cargo, in the case of SNX27, at the early endosomal membrane (Balana et al, 2011;Bottcher et al, 2012;Cai et al, 2011;Ghai et al, 2013;Hayashi et al, 2012;Joubert et al, 2004;Knauth et al, 2005;Lauffer et al, 2010;Lunn et al, 2007;Steinberg et al, 2013;Temkin et al, 2011;Valdes et al, 2011;Wang et al, 2013). This influences the routing of transmembrane cargo trafficking, away from degradative late endosomes and into recycling and retrieval pathways from the endosome back to the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have found that, upon T-cell activation, SNX27 is sorted into two pools at the immunological synapse, where it is found at both the plasma membrane and on transferrin receptor (TfR)-positive intracellular vesicles thought to be recycling endosomes Rincón et al, 2011;Rincón et al, 2007). In addition, SNX27 was also found in plasma-membrane-enriched membrane fractions in cell surface biotinylation experiments (Hayashi et al, 2012). The mechanism of SNX27 relocalization to the immunological synapse remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, sorting nexin 27, a member of the sorting nexin family of proteins known to be involved in the cellular trafficking and sorting of cargo proteins, also binds to cell surface MRP4 and increases its internalization. 26 Therefore, it is possible that NHERF3 expression may inhibit the associations between these internalization-promoting PDZ proteins and MRP4. Especially in cells that express both NHERF1 and NHERF3, such as kidney tubules, ablation of NHERF3 may play a particularly important role in disrupting the balance between the MRP4-NHERF1 and MRP4-NHERF3 associations, increasing the internalization and degradation of MRP4.…”
Section: Discussionmentioning
confidence: 99%